Self-compacting concrete and preparation method thereof

By using composite raw materials and modified functional agents in self-finished concrete, the problems of aggregate settlement and cement hydration heat aggregation are solved, and the mechanical properties and crack resistance and compression resistance of concrete are significantly improved.

CN116589254BActive Publication Date: 2025-04-01SHANDONG EXPRESSWAY INFRASTRUCTURE CONSTR CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310683317.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-09
Publication Date
2025-04-01
Estimated Expiration
2043-06-09

AI Technical Summary

Technical Problem

The existing self-finished concrete has deteriorated mechanical properties due to aggregate settlement after pouring, and the heat accumulation caused by cement hydration leads to internal and external temperature differences, which can easily cause concrete cracking and affect strength performance.

Method used

The composite of fly ash, sand, gravel and limestone ore powder is used, and the modified dual-modification functional agent of cement and whiskers is combined with the modified dual-modification functional agent. The concentrated nitric acid reflux pretreatment of silicon carbide whiskers and the ball milling of nanogenic agent blending organic alcohol amine agent is improved to improve the matrix material strength and coagulation capacity of concrete, and the fibre additives are blended with hollow glass microbeads.

Benefits of technology

It effectively reduces the settlement degree of aggregate, improves the cement hydration heat dissipation efficiency, coordinates and improves the mechanical properties of concrete, and improves the cracking and compressive strength properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004277505390000171
    Figure BDA0004277505390000171
  • Figure BDA0004277505390000191
    Figure BDA0004277505390000191
Patent Text Reader

Abstract

The invention relates to the technical field of self-compacting concrete, and specifically discloses a self-compacting concrete, comprising the following raw materials by weight: 65-75 parts of cement, 35-40 parts of fly ash, 25-30 parts of sand, 25-30 parts of crushed stone, 15-20 parts of limestone powder, 10-15 parts of whisker compound modified double-adjusting functional agent, 4-8 parts of hollow glass microsphere blending fiber additive, 2-3 parts of water reducer, and 85-95 parts of water. The hollow glass microsphere blending fiber additive prepared by the invention is formulated in the system, and can synergize with the whisker compound modified double-adjusting functional agent to jointly enhance the performance effect of the product, and further improve the anti-cracking and compressive strength performance effect of the product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, and in particular to a self-compacting concrete and a preparation method thereof. Background Art

[0002] Concrete is a general term for engineering composite materials that are made of cementitious materials to bind aggregates into a whole. It is widely used in civil engineering. Self-compacting concrete is widely used in secondary pouring outside the insulation of concrete walls, as well as in areas where the reinforcement is dense and cannot be vibrated. Self-compacting concrete mixture has sufficient plastic viscosity. It can flow and fill densely under its own weight during pouring. It can also completely fill the formwork in dense steel bars to obtain good homogeneity.

[0003] Since the existing self-compacting concrete adopts a multi-phase mixing system, the density difference between the cement slurry and the aggregate raw materials easily causes the aggregate to settle at the bottom of the concrete when it is left stationary after pouring, thereby causing the mechanical properties of the concrete to deteriorate. At the same time, heat accumulation is generated during cement hydration, resulting in a temperature difference between the inside and outside, which easily causes the concrete to crack, further affecting the strength performance of the concrete. Based on this, the present invention further improves it. Summary of the invention

[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a self-compacting concrete and a preparation method thereof to solve the problems raised in the above background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution:

[0006] The present invention provides a self-compacting concrete, comprising the following raw materials in parts by weight:

[0007] 65-75 parts of cement, 35-40 parts of fly ash, 25-30 parts of sand, 25-30 parts of crushed stone, 15-20 parts of limestone powder, 10-15 parts of whisker compound modified double-adjusting functional agent, 4-8 parts of hollow glass microspheres and fiber additives, 2-3 parts of water reducer, and 85-95 parts of water.

[0008] Preferably, the self-compacting concrete comprises the following raw materials in parts by weight:

[0009] 70 parts of cement, 37.5 parts of fly ash, 27.5 parts of sand, 27.5 parts of crushed stone, 17.5 parts of limestone powder, 12.5 parts of whisker compound modified double-adjusting functional agent, 6 parts of hollow glass microsphere blending fiber additive, 2.5 parts of water reducing agent, and 90 parts of water.

[0010] Preferably, the cement is one or more combinations of silicate cement, aluminate cement, sulphoaluminate cement and ferroaluminate cement;

[0011] The fly ash is Class I fly ash, with a 45 μm sieve residue of ≤12% and a moisture content of ≤1.0; the fineness modulus of the sand is 2.5-3.0, and the apparent density is 2600-2620 kg / m 3 The crushed stone is a continuously graded crushed stone with a particle size of 5 to 10 mm and an apparent density of 2650 to 2680 kg / m 3 The water reducer is a polycarboxylic acid-based high-performance water reducer with a water reduction rate of ≥30%; the particle size of the limestone powder is 2 to 2.5 mm.

[0012] Preferably, the preparation method of the whisker-compounded modified dual-adjustment functional agent is:

[0013] S01: Sodium dodecyl sulfate and deionized water are mixed uniformly in a weight ratio of 1:5, and then 10-15% of the total amount of sodium dodecyl sulfate and 2-5% of the total amount of sodium dodecyl sulfate and 6% yttrium nitrate solution are added, and stirred sufficiently to obtain sodium dodecyl sulfate solution;

[0014] S02: placing the silicon carbide whisker in 3 to 5 times concentrated nitric acid for reflux pretreatment, then adding the refluxed silicon carbide whisker to a 2% hydrochloric acid solution at a weight ratio of 1:5 and stirring to disperse evenly, then adding 10 to 15% of the total amount of the refluxed silicon carbide whisker sodium dodecyl sulfate solution, stirring and reacting, and after the reaction is completed, washing with water and drying to obtain a silicon carbide whisker pre-adjustment;

[0015] S03: Preparation of nano-agent and organic alcohol amine agent:

[0016] S031: adding 3% to 6% of the total amount of a phosphate buffer solution with a pH value of 5.0 to a 10% to 15% mass fraction organic alcohol amine aqueous solution, and stirring to mix uniformly;

[0017] S032: then add 5-9% of the total amount of the organic alcohol amine aqueous solution of the blending modifier and 1-3% of the total amount of the organic alcohol amine aqueous solution of the lanthanum nitrate solution to S031, and stir at a speed of 350-450r / min for 20-30min;

[0018] S033: Finally, add 5-10% of the total amount of organic alcohol amine aqueous solution of sodium humate and 1-2% of the total amount of organic alcohol amine aqueous solution of nanocellulose to S032, and then stir at a speed of 650-750 r / min for 30-40 minutes. After stirring, the nano agent and organic alcohol amine agent are obtained;

[0019] S04: Add nano-agent and organic alcohol amine agent to the silicon carbide whisker pre-adjustment according to a weight ratio of 7:2, transfer to a ball mill for ball milling, the ball milling speed is 1000-1500r / min, the ball milling is 1-2h, after the ball milling is completed, wash with water, and dry to obtain a whisker composite modified dual-adjustment functional agent.

[0020] Preferably, the temperature of the reflux pretreatment in S02 is 65-68°C, the reflux time is 2-3h, and after the reflux is completed, the boiling water washing is repeated 2-3 times, and the treatment is completed;

[0021] The stirring reaction temperature in S02 is 40-45°C, the stirring time is 25-35min, and the stirring speed is 300-400r / min.

[0022] Preferably, the organic alcohol amine in the organic alcohol amine aqueous solution is one of monoethanolamine, propanolamine and butanolamine; and the mass fraction of the lanthanum nitrate solution is 2-4%.

[0023] Preferably, the preparation method of the blending modifier is:

[0024] The carbon nanotubes are first heated to 55-60°C for 10-20 minutes, then kept warm, and the soaking liquid is sprayed on the surface of the carbon nanotubes to soak them; wherein the soaking liquid is an aqueous solution of sodium silicate with a mass fraction of 8%;

[0025] Then the temperature is raised to 75-78°C at a rate of 1-3°C / min, kept warm for 5-10 minutes, and finally dispersed and cooled in a 5% by mass sodium alginate aqueous solution. The speed of the dispersed cooling is 500-700r / min, and the treatment time is 75-85min. After the treatment is completed, it is washed with water and dried to obtain a blending modifier.

[0026] Preferably, the preparation method of the hollow glass microsphere blending fiber additive is:

[0027] S11: Preparation of hydroxyapatite fibers:

[0028] Mix polycaprolactone and polyethylene glycol in a weight ratio of 4:2, add the mixture into an ethanol solvent that is 5 times the total amount of polycaprolactone, and stir evenly to obtain a primary solution;

[0029] Adding 15-25% of the total amount of the initial solution of nano-hydroxyapatite to the initial solution, stirring evenly, to obtain nano-hydroxyapatite body; electrospinning the nano-hydroxyapatite body under the conditions of voltage of 30-35kv and flow rate of 5-9ml / h to obtain hydroxyapatite fiber;

[0030] S12: Add 1 to 3 parts of carboxymethyl cellulose, 2 to 5 parts of 5% by mass chitosan aqueous solution and 0.8 to 1.2 parts of hydroxyapatite fiber to 5 to 10 parts of hollow glass microspheres, send them into a ball mill for ball milling, wash and dry them after the ball milling is completed to obtain hollow glass microspheres and fiber additives.

[0031] Preferably, the ball milling speed of the ball milling treatment is 1000-1200 r / min, and the ball milling time is 1-1.5 h.

[0032] The present invention also provides a method for preparing self-compacting concrete, comprising the following steps:

[0033] Step 1: Add fly ash, sand, crushed stone and limestone powder into a mixer and disperse them at a speed of 1200-1500 r / min for 5-10 minutes to prepare an aggregate agent;

[0034] Step 2: Stir and mix the whisker compound modified double-adjusting functional agent, hollow glass microspheres and fiber additives evenly, then add them to the aggregate agent, then add cement to the aggregate agent, and disperse at a speed of 500-600r / min for 35-40min;

[0035] Step 3: Then add water and a water reducing agent to the product of step 2, and continue stirring for 10 to 15 minutes to obtain the self-compacting concrete of the present invention.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] 1. The self-compacting concrete of the present invention adopts fly ash, sand, crushed stone and limestone powder as raw materials, and then mixes with cement to obtain a matrix material that can provide basic strength performance support for concrete products. The whisker compound modified double-adjustment functional agent is added to prepare the concrete base material. The whisker compound modified double-adjustment functional agent adopts silicon carbide whiskers and is pre-treated by concentrated nitric acid reflux. The activity of the treated whiskers is enhanced. At the same time, in the stirring reaction modification of hydrochloric acid solution and sodium dodecyl sulfate solution, the distribution and activity of the whiskers are improved. The whisker pre-adjustment agent after pretreatment is combined with the nano agent to adjust the organic The ball milling of the alcohol amine agent is improved, and the compounding and blending effect is improved. The improved whisker compounding and modified double-adjusting functional agent is distributed in the base material, which can provide high-quality support for the base material, reduce the sedimentation of the product, and improve the cement hydration and heat dissipation efficiency, coordinate and improve the performance of the product. At the same time, the product's anti-cracking and compressive strength performance are also improved. In addition, the hollow glass microspheres and fiber additives are formulated in the system, which can synergize with the whisker compounding and modified double-adjusting functional agent to jointly enhance the performance of the product, and further improve the product's anti-cracking and compressive strength performance effects;

[0038] 2. Nano-agent blending organic alcohol amine agent uses organic alcohol amine aqueous solution as the base material, and first stirs and mixes evenly through phosphate buffer solution; then coordinates with blending modifier and lanthanum nitrate solution for preliminary stirring, and then coordinates with sodium humate and nano-cellulose for secondary stirring. Lanthanum nitrate solution, nano-cellulose coordinated with sodium humate and phosphate buffer solution can improve the activity of organic alcohol amine, make the organic alcohol amine complexing ability stronger, and promote the coagulation ability of concrete. The whisker pre-adjuster is matched in the nano-agent blending organic alcohol amine agent, and the settlement of aggregate is inhibited through the distribution of whiskers. Through the joint coordination and deployment of the raw materials, the performance of the product is further improved;

[0039] 3. In addition, the blending modifier adopts carbon nanotubes, which are preheated, sprayed with the immersion liquid, and then heated for optimization and improvement, and finally cooled and dispersed. The activity of the preheated carbon nanotubes is improved, the immersion liquid is sprayed, and the carbon nanotubes are coated with the sodium silicate solution, so that the blending modifier is more stably distributed in the nano-agent blending organic alcohol amine agent, and then with the subsequent temperature optimization, cooling and dispersion, the dispersion of the blending modifier is improved, so that the coordinated and optimized nano-agent blending organic alcohol amine agent has a lower sedimentation inhibition performance on aggregates, and through the optimization treatment of carbon nanotubes, the heat accumulated in the concrete can be transferred, and the heat dissipation effect is significantly improved. The raw materials of the nano-agent blending organic alcohol amine agent are mutually allocated, coordinated, and synergistic, so as to achieve the coordinated improvement of the performance of the product, and then the anti-cracking performance and compressive strength of the product are significantly improved;

[0040] 4. Hollow glass microspheres and fiber additives are prepared by ball-milling modification with carboxymethyl cellulose, chitosan aqueous solution and hydroxyapatite fibers. The modified hollow glass microspheres and fiber additives are filled in the concrete product system to enhance the performance of the product and coordinate with the whisker-compounded modified double-adjusting functional agent to further optimize the performance of the product. DETAILED DESCRIPTION

[0041] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] A self-compacting concrete of this embodiment includes the following raw materials in parts by weight:

[0043] 65-75 parts of cement, 35-40 parts of fly ash, 25-30 parts of sand, 25-30 parts of crushed stone, 15-20 parts of limestone powder, 10-15 parts of whisker compound modified double-adjusting functional agent, 4-8 parts of hollow glass microspheres and fiber additives, 2-3 parts of water reducer, and 85-95 parts of water.

[0044] The self-compacting concrete of this embodiment includes the following raw materials in parts by weight:

[0045] 70 parts of cement, 37.5 parts of fly ash, 27.5 parts of sand, 27.5 parts of crushed stone, 17.5 parts of limestone powder, 12.5 parts of whisker compound modified double-adjusting functional agent, 6 parts of hollow glass microsphere blending fiber additive, 2.5 parts of water reducing agent, and 90 parts of water.

[0046] The cement in this embodiment is one or more combinations of silicate cement, aluminate cement, sulphoaluminate cement and ferroaluminate cement;

[0047] The fly ash is Class I fly ash, with a 45 μm sieve residue of ≤12% and a moisture content of ≤1.0; the fineness modulus of the sand is 2.5-3.0, and the apparent density is 2600-2620 kg / m 3 The crushed stone is a continuously graded crushed stone with a particle size of 5 to 10 mm and an apparent density of 2650 to 2680 kg / m 3 The water reducer is a polycarboxylic acid-based high-performance water reducer with a water reduction rate of ≥30%; the particle size of the limestone powder is 2 to 2.5 mm.

[0048] The preparation method of the whisker composite modified dual-tuning functional agent of this embodiment is:

[0049] S01: Sodium dodecyl sulfate and deionized water are mixed uniformly in a weight ratio of 1:5, and then 10-15% of the total amount of sodium dodecyl sulfate and 2-5% of the total amount of sodium dodecyl sulfate and 6% yttrium nitrate solution are added, and stirred sufficiently to obtain sodium dodecyl sulfate solution;

[0050] S02: placing the silicon carbide whisker in 3 to 5 times concentrated nitric acid for reflux pretreatment, then adding the refluxed silicon carbide whisker to a 2% hydrochloric acid solution at a weight ratio of 1:5 and stirring to disperse evenly, then adding 10 to 15% of the total amount of the refluxed silicon carbide whisker sodium dodecyl sulfate solution, stirring and reacting, and after the reaction is completed, washing with water and drying to obtain a silicon carbide whisker pre-adjustment;

[0051] S03: Preparation of nano-agent and organic alcohol amine agent:

[0052] S031: adding 3% to 6% of the total amount of a phosphate buffer solution with a pH value of 5.0 to a 10% to 15% mass fraction organic alcohol amine aqueous solution, and stirring to mix uniformly;

[0053] S032: then add 5-9% of the total amount of the organic alcohol amine aqueous solution of the blending modifier and 1-3% of the total amount of the organic alcohol amine aqueous solution of the lanthanum nitrate solution to S031, and stir at a speed of 350-450r / min for 20-30min;

[0054] S033: Finally, add 5-10% of the total amount of organic alcohol amine aqueous solution of sodium humate and 1-2% of the total amount of organic alcohol amine aqueous solution of nanocellulose to S032, and then stir at a speed of 650-750 r / min for 30-40 minutes. After stirring, the nano agent and organic alcohol amine agent are obtained;

[0055] S04: Add nano-agent and organic alcohol amine agent to the silicon carbide whisker pre-adjustment according to a weight ratio of 7:2, transfer to a ball mill for ball milling, the ball milling speed is 1000-1500r / min, the ball milling is 1-2h, after the ball milling is completed, wash with water, and dry to obtain a whisker composite modified dual-adjustment functional agent.

[0056] In S02 of this embodiment, the temperature of the reflux pretreatment is 65-68°C, the reflux time is 2-3h, and after the reflux is completed, the boiling water washing is repeated 2-3 times, and the treatment is completed;

[0057] The stirring reaction temperature in S02 is 40-45°C, the stirring time is 25-35min, and the stirring speed is 300-400r / min.

[0058] The organic alcohol amine in the organic alcohol amine aqueous solution of the present embodiment is one of monoethanolamine, propanolamine and butanolamine; the mass fraction of the lanthanum nitrate solution is 2-4%.

[0059] The preparation method of the blending modifier of this embodiment is:

[0060] The carbon nanotubes are first heated to 55-60°C for 10-20 minutes, then kept warm, and the soaking liquid is sprayed on the surface of the carbon nanotubes to soak them; wherein the soaking liquid is an aqueous sodium silicate solution with a mass fraction of 8%;

[0061] Then the temperature is raised to 75-78°C at a rate of 1-3°C / min, kept warm for 5-10 minutes, and finally dispersed and cooled in a 5% by mass sodium alginate aqueous solution. The speed of the dispersed cooling is 500-700r / min, and the treatment time is 75-85min. After the treatment is completed, it is washed with water and dried to obtain a blending modifier.

[0062] The preparation method of the hollow glass microsphere blending fiber additive of this embodiment is:

[0063] S11: Preparation of hydroxyapatite fibers:

[0064] Mix polycaprolactone and polyethylene glycol in a weight ratio of 4:2, add the mixture into an ethanol solvent that is 5 times the total amount of polycaprolactone, and stir evenly to obtain a primary solution;

[0065] Adding 15-25% of the total amount of the initial solution of nano-hydroxyapatite to the initial solution, stirring evenly, to obtain nano-hydroxyapatite body; electrospinning the nano-hydroxyapatite body under the conditions of voltage of 30-35kv and flow rate of 5-9ml / h to obtain hydroxyapatite fiber;

[0066] S12: Add 1 to 3 parts of carboxymethyl cellulose, 2 to 5 parts of 5% by mass chitosan aqueous solution and 0.8 to 1.2 parts of hydroxyapatite fiber to 5 to 10 parts of hollow glass microspheres, send them into a ball mill for ball milling, wash and dry them after the ball milling is completed to obtain hollow glass microspheres and fiber additives.

[0067] The ball milling speed of the ball milling treatment in this embodiment is 1000-1200 r / min, and the ball milling is 1-1.5 hours.

[0068] A method for preparing a self-compacting concrete in this embodiment comprises the following steps:

[0069] Step 1: Add fly ash, sand, crushed stone and limestone powder into a mixer and disperse them at a speed of 1200-1500 r / min for 5-10 minutes to prepare an aggregate agent;

[0070] Step 2: Stir and mix the whisker compound modified double-adjusting functional agent, hollow glass microspheres and fiber additives evenly, then add them to the aggregate agent, then add cement to the aggregate agent, and disperse at a speed of 500-600r / min for 35-40min;

[0071] Step 3: Then add water and a water reducing agent to the product of step 2, and continue stirring for 10 to 15 minutes to obtain the self-compacting concrete of the present invention.

[0072] Example 1.

[0073] A self-compacting concrete of this embodiment includes the following raw materials in parts by weight:

[0074] 65 parts of cement, 35 parts of fly ash, 25 parts of sand, 25 parts of crushed stone, 15 parts of limestone powder, 10 parts of whisker compound modified double-adjusting functional agent, 4 parts of hollow glass microsphere blending fiber additive, 2 parts of water reducer, and 85 parts of water.

[0075] The cement in this embodiment is one or more combinations of silicate cement, aluminate cement, sulphoaluminate cement and ferroaluminate cement;

[0076] The fly ash is Class I fly ash, with a 45 μm sieve residue of ≤12% and a moisture content of ≤1.0; the fineness modulus of the sand is 2.5 and the apparent density is 2600 kg / m 3 The crushed stone is a continuous graded crushed stone with a particle size of 5 mm and an apparent density of 2650 kg / m 3 The water reducer is a polycarboxylic acid-based high-performance water reducer with a water reduction rate of ≥30%; the particle size of the limestone powder is 2 mm.

[0077] The preparation method of the whisker composite modified dual-tuning functional agent of this embodiment is:

[0078] S01: Sodium dodecyl sulfate and deionized water are mixed uniformly in a weight ratio of 1:5, and then 10% of the total amount of sodium dodecyl sulfate and 2% of the total amount of sodium dodecyl sulfate and 6% yttrium nitrate solution are added, and stirred sufficiently to obtain sodium dodecyl sulfate solution;

[0079] S02: placing the silicon carbide whisker in 3 times concentrated nitric acid for reflux pretreatment, then adding the refluxed silicon carbide whisker to a 2% hydrochloric acid solution at a weight ratio of 1:5 and stirring to disperse evenly, then adding sodium dodecyl sulfate solution of 10% of the total amount of the refluxed silicon carbide whisker, stirring for reaction treatment, and washing and drying after the reaction is completed to obtain a silicon carbide whisker pre-adjustment;

[0080] S03: Preparation of nano-agent and organic alcohol amine agent:

[0081] S031: adding 3% of the total amount of phosphate buffer solution with a pH value of 5.0 in the organic alcohol amine aqueous solution to a 10% by mass fraction organic alcohol amine aqueous solution, and stirring to mix evenly;

[0082] S032: Then add 5% of the total amount of the organic alcohol amine aqueous solution of the blending modifier and 1% of the total amount of the organic alcohol amine aqueous solution of the lanthanum nitrate solution to S031, and stir at a speed of 350r / min for 20min;

[0083] S033: Finally, add 5% of the total amount of organic alcohol amine aqueous solution of sodium humate and 1% of the total amount of organic alcohol amine aqueous solution of nanocellulose to S032, and stir at a speed of 650r / min for 30min. After stirring, the nano agent and organic alcohol amine agent are obtained;

[0084] S04: Add nano-agent and organic alcohol amine agent to the silicon carbide whisker pre-adjustment according to the weight ratio of 7:2, transfer to a ball mill for ball milling, the ball milling speed is 1000r / min, the ball milling is for 1h, after the ball milling is completed, wash with water, and dry to obtain a whisker composite modified dual-adjustment functional agent.

[0085] In S02 of this embodiment, the temperature of the reflux pretreatment is 65°C, the reflux time is 2h, and after the reflux is completed, the boiling water washing is repeated twice, and the treatment is completed;

[0086] The stirring reaction temperature in S02 is 40°C, the stirring time is 25min, and the stirring speed is 300r / min.

[0087] The organic alcohol amine in the organic alcohol amine aqueous solution of this embodiment is monoethanolamine; the mass fraction of the lanthanum nitrate solution is 2%.

[0088] The preparation method of the blending modifier of this embodiment is:

[0089] The carbon nanotubes are first heated to 55°C for 10 minutes, then kept warm, and the soaking liquid is sprayed on the surface of the carbon nanotubes to soak them; wherein the soaking liquid is a sodium silicate aqueous solution with a mass fraction of 8%;

[0090] Then the temperature is raised to 75°C at a rate of 1°C / min, kept warm for 5 minutes, and finally dispersed and cooled in a 5% by mass sodium alginate aqueous solution. The speed of the dispersed cooling is 500r / min and the treatment time is 75 minutes. After the treatment is completed, it is washed with water and dried to obtain a blending modifier.

[0091] The preparation method of the hollow glass microsphere blending fiber additive of this embodiment is:

[0092] S11: Preparation of hydroxyapatite fibers:

[0093] Mix polycaprolactone and polyethylene glycol in a weight ratio of 4:2, add the mixture into an ethanol solvent that is 5 times the total amount of polycaprolactone, and stir evenly to obtain a primary solution;

[0094] Adding 15% of the total amount of the initial solution of nano-hydroxyapatite to the initial solution, stirring evenly, to obtain nano-hydroxyapatite body; electrospinning the nano-hydroxyapatite body under the conditions of voltage of 30 kV and flow rate of 5 ml / h to obtain hydroxyapatite fiber;

[0095] S12: Add 1 part of carboxymethyl cellulose, 2 parts of 5% by mass chitosan aqueous solution and 0.8 parts of hydroxyapatite fiber to 5 parts of hollow glass microspheres, send them into a ball mill for ball milling, wash with water and dry them to obtain hollow glass microspheres and fiber additives.

[0096] The ball milling speed of the ball milling treatment in this embodiment is 1000 r / min, and the ball milling is 1 hour.

[0097] A method for preparing a self-compacting concrete in this embodiment comprises the following steps:

[0098] Step 1: Add fly ash, sand, crushed stone and limestone powder into a mixer and disperse at a speed of 1200r / min for 5 minutes to prepare an aggregate agent;

[0099] Step 2: Stir and mix the whisker compound modified double-adjusting functional agent, hollow glass microspheres and fiber additives evenly, then add them to the aggregate agent, then add cement to the aggregate agent, and disperse at a speed of 500r / min for 35min;

[0100] Step 3: Then add water and a water reducing agent to the product of step 2, and continue stirring for 10 minutes to obtain the self-compacting concrete of the present invention.

[0101] Example 2.

[0102] A self-compacting concrete of this embodiment includes the following raw materials in parts by weight:

[0103] 75 parts of cement, 40 parts of fly ash, 30 parts of sand, 30 parts of crushed stone, 20 parts of limestone powder, 15 parts of whisker compound modified double-adjusting functional agent, 8 parts of hollow glass microsphere blending fiber additive, 3 parts of water reducing agent, and 95 parts of water.

[0104] The cement in this embodiment is one or more combinations of silicate cement, aluminate cement, sulphoaluminate cement and ferroaluminate cement;

[0105] The fly ash is Class I fly ash, with a 45 μm sieve residue of ≤12% and a moisture content of ≤1.0; the fineness modulus of the sand is 3.0 and the apparent density is 2620 kg / m 3 The crushed stone is a continuously graded crushed stone with a particle size of 10 mm and an apparent density of 2680 kg / m 3 The water reducer is a polycarboxylic acid-based high-performance water reducer with a water reduction rate of ≥30%; the particle size of the limestone powder is 2.5 mm.

[0106] The preparation method of the whisker composite modified dual-tuning functional agent of this embodiment is:

[0107] S01: Sodium dodecyl sulfate and deionized water are mixed uniformly in a weight ratio of 1:5, and then 15% of the total amount of sodium dodecyl sulfate and 5% of the total amount of sodium dodecyl sulfate and 6% yttrium nitrate solution are added, and stirred sufficiently to obtain sodium dodecyl sulfate solution;

[0108] S02: placing the silicon carbide whisker in 5 times concentrated nitric acid for reflux pretreatment, then adding the refluxed silicon carbide whisker to a 2% hydrochloric acid solution at a weight ratio of 1:5 and stirring to disperse evenly, then adding 15% sodium dodecyl sulfate solution of the total amount of the refluxed silicon carbide whisker, stirring for reaction treatment, and washing and drying after the reaction is completed to obtain a silicon carbide whisker pre-adjustment;

[0109] S03: Preparation of nano-agent and organic alcohol amine agent:

[0110] S031: Add 6% of the total amount of phosphate buffer solution with a pH value of 5.0 to the 15% by mass organic alcohol amine aqueous solution, and stir to mix evenly;

[0111] S032: Then add 9% of the total amount of the organic alcohol amine aqueous solution of the blending modifier and 3% of the total amount of the organic alcohol amine aqueous solution of the lanthanum nitrate solution to S031, and stir at a speed of 450r / min for 30min;

[0112] S033: Finally, add 10% of sodium humate and 2% of nanocellulose in the total amount of the organic alcohol amine aqueous solution to S032, and stir at a speed of 750 r / min for 30 to 40 minutes. After stirring, the nano-agent and organic alcohol amine agent are obtained;

[0113] S04: Add nano-agent and organic alcohol amine agent to the silicon carbide whisker pre-adjustment according to the weight ratio of 7:2, transfer to a ball mill for ball milling, the ball milling speed is 1500r / min, the ball milling is carried out for 2h, and after the ball milling is completed, the mixture is washed with water and dried to obtain a whisker composite modified dual-adjustment functional agent.

[0114] In S02 of this embodiment, the temperature of the reflux pretreatment is 68°C, the reflux time is 3h, and after the reflux is completed, the boiling water washing is repeated 3 times, and the treatment is completed;

[0115] The stirring reaction temperature in S02 is 45°C, the stirring time is 35min, and the stirring speed is 400r / min.

[0116] The organic alcohol amine in the organic alcohol amine aqueous solution of this embodiment is propanolamine; the mass fraction of the lanthanum nitrate solution is 4%.

[0117] The preparation method of the blending modifier of this embodiment is:

[0118] The carbon nanotubes are first heated to 60°C for 20 minutes, then kept warm, and the soaking liquid is sprayed on the surface of the carbon nanotubes to soak them; wherein the soaking liquid is a sodium silicate aqueous solution with a mass fraction of 8%;

[0119] Then the temperature is raised to 78°C at a rate of 3°C / min, kept warm for 10 minutes, and finally dispersed and cooled in a 5% by mass sodium alginate aqueous solution. The speed of the dispersed cooling is 700r / min and the treatment time is 85min. After the treatment is completed, it is washed with water and dried to obtain a blending modifier.

[0120] The preparation method of the hollow glass microsphere blending fiber additive of this embodiment is:

[0121] S11: Preparation of hydroxyapatite fibers:

[0122] Mix polycaprolactone and polyethylene glycol in a weight ratio of 4:2, add the mixture into an ethanol solvent that is 5 times the total amount of polycaprolactone, and stir evenly to obtain a primary solution;

[0123] Adding 25% of the total amount of the initial solution of nano-hydroxyapatite to the initial solution, stirring evenly, to obtain nano-hydroxyapatite bodies; electrospinning the nano-hydroxyapatite bodies under the conditions of a voltage of 35 kV and a flow rate of 9 ml / h to obtain hydroxyapatite fibers;

[0124] S12: Add 3 parts of carboxymethyl cellulose, 5 parts of 5% by mass chitosan aqueous solution and 1.2 parts of hydroxyapatite fiber to 10 parts of hollow glass microspheres, send them into a ball mill for ball milling, wash with water and dry them to obtain hollow glass microspheres and fiber additives.

[0125] The ball milling speed of the ball milling treatment in this embodiment is 1200 r / min, and the ball milling is 1.5 h.

[0126] A method for preparing a self-compacting concrete in this embodiment comprises the following steps:

[0127] Step 1: Add fly ash, sand, crushed stone and limestone powder into a mixer and disperse at a speed of 1500r / min for 10min to prepare an aggregate agent;

[0128] Step 2: Stir and mix the whisker compound modified double-adjusting functional agent, hollow glass microspheres and fiber additives evenly, then add them to the aggregate agent, then add cement to the aggregate agent, and disperse at a speed of 600r / min for 40min;

[0129] Step 3: Then add water and a water reducing agent to the product of step 2, and continue stirring for 15 minutes to obtain the self-compacting concrete of the present invention.

[0130] Example 3.

[0131] A self-compacting concrete of this embodiment includes the following raw materials in parts by weight:

[0132] 70 parts of cement, 37.5 parts of fly ash, 27.5 parts of sand, 27.5 parts of crushed stone, 17.5 parts of limestone powder, 12.5 parts of whisker compound modified double-adjusting functional agent, 6 parts of hollow glass microsphere blending fiber additive, 2.5 parts of water reducing agent, and 90 parts of water.

[0133] The cement in this embodiment is one or more combinations of silicate cement, aluminate cement, sulphoaluminate cement and ferroaluminate cement;

[0134] The fly ash is Class I fly ash, with a 45 μm sieve residue of ≤12% and a moisture content of ≤1.0; the fineness modulus of the sand is 2.75 and the apparent density is 2610 kg / m 3 The crushed stone is a continuously graded crushed stone with a particle size of 7.5 mm and an apparent density of 2670 kg / m 3 The water reducer is a polycarboxylic acid-based high-performance water reducer with a water reduction rate of ≥30%; the particle size of the limestone powder is 2.2 mm.

[0135] The preparation method of the whisker composite modified dual-tuning functional agent of this embodiment is:

[0136] S01: Sodium dodecyl sulfate and deionized water are mixed uniformly in a weight ratio of 1:5, and then citric acid (12% of the total amount of sodium dodecyl sulfate) and yttrium nitrate solution (6% by mass) (3.5% of the total amount of sodium dodecyl sulfate) are added, and stirred sufficiently to obtain a sodium dodecyl sulfate solution;

[0137] S02: placing the silicon carbide whisker in 4 times concentrated nitric acid for reflux pretreatment, then adding the refluxed silicon carbide whisker to a 2% hydrochloric acid solution at a weight ratio of 1:5 and stirring to disperse evenly, then adding 12% sodium dodecyl sulfate solution of the total amount of the refluxed silicon carbide whisker, stirring for reaction treatment, and washing and drying after the reaction is completed to obtain a silicon carbide whisker pre-adjustment;

[0138] S03: Preparation of nano-agent and organic alcohol amine agent:

[0139] S031: Add 4.5% of the total amount of phosphate buffer solution with a pH value of 5.0 to the 12.5% ​​by mass fraction organic alcohol amine aqueous solution, and stir to mix evenly;

[0140] S032: Then add 7% of the total amount of the organic alcohol amine aqueous solution of the blending modifier and 2% of the total amount of the organic alcohol amine aqueous solution of the lanthanum nitrate solution to S031, and stir at a speed of 400r / min for 25min;

[0141] S033: Finally, add 7.5% of sodium humate and 1.5% of nanocellulose in the total amount of the organic alcohol amine aqueous solution to S032, and stir at a speed of 700 r / min for 35 minutes. After stirring, the nano-agent and the organic alcohol amine agent are obtained;

[0142] S04: Add nano-agent and organic alcohol amine agent to the silicon carbide whisker pre-adjustment in a weight ratio of 7:2, transfer to a ball mill for ball milling, the ball milling speed is 1250r / min, the ball milling is performed for 1.5h, and after the ball milling is completed, the mixture is washed with water and dried to obtain a whisker composite modified dual-adjustment functional agent.

[0143] In S02 of this embodiment, the temperature of the reflux pretreatment is 66°C, the reflux time is 2.5h, and after the reflux is completed, the boiling water washing is repeated twice, and the treatment is completed;

[0144] The stirring reaction temperature in S02 is 42.5°C, the stirring time is 28min, and the stirring speed is 350r / min.

[0145] The organic alcoholamine in the organic alcoholamine aqueous solution of the present embodiment is one of monoethanolamine, propanolamine and butanolamine; and the mass fraction of the lanthanum nitrate solution is 3%.

[0146] The preparation method of the blending modifier of this embodiment is:

[0147] The carbon nanotubes are first heated to 58°C for 10 to 20 minutes, then kept warm, and the soaking liquid is sprayed on the surface of the carbon nanotubes to soak them; wherein the soaking liquid is an aqueous sodium silicate solution with a mass fraction of 8%;

[0148] Then the temperature is raised to 76°C at a rate of 2°C / min, kept warm for 7.5 minutes, and finally dispersed and cooled in a 5% by mass sodium alginate aqueous solution. The speed of the dispersed cooling is 650r / min, and the treatment time is 80 minutes. After the treatment is completed, it is washed with water and dried to obtain a blending modifier.

[0149] The preparation method of the hollow glass microsphere blending fiber additive of this embodiment is:

[0150] S11: Preparation of hydroxyapatite fibers:

[0151] Mix polycaprolactone and polyethylene glycol in a weight ratio of 4:2, add the mixture into an ethanol solvent that is 5 times the total amount of polycaprolactone, and stir evenly to obtain a primary solution;

[0152] Adding 20% ​​of the total amount of the initial solution of nano-hydroxyapatite to the initial solution, stirring evenly, to obtain nano-hydroxyapatite body; electrospinning the nano-hydroxyapatite body under the conditions of voltage of 32kv and flow rate of 7ml / h to obtain hydroxyapatite fiber;

[0153] S12: Add 2 parts of carboxymethyl cellulose, 3.5 parts of 5% chitosan aqueous solution by mass and 1.0 part of hydroxyapatite fiber to 7.5 parts of hollow glass microspheres, send into a ball mill for ball milling, wash with water and dry to obtain hollow glass microspheres and fiber additives.

[0154] The ball milling speed of the ball milling treatment in this embodiment is 1100 r / min, and the ball milling is 1.2 h.

[0155] A method for preparing a self-compacting concrete in this embodiment comprises the following steps:

[0156] Step 1: Add fly ash, sand, crushed stone and limestone powder into a mixer and disperse at a speed of 1350r / min for 7.5min to prepare an aggregate agent;

[0157] Step 2: Stir and mix the whisker compound modified double-adjusting functional agent, hollow glass microspheres and fiber additives evenly, then add them to the aggregate agent, then add cement to the aggregate agent, and disperse at a speed of 550r / min for 38min;

[0158] Step 3: Then add water and a water reducing agent to the product of step 2, and continue stirring for 12.5 minutes to obtain the self-compacting concrete of the present invention.

[0159] Comparative Example 1.

[0160] The difference from Example 3 is that the whisker-compounded modified dual-tuning functional agent is not added.

[0161] Comparative Example 2.

[0162] The difference from Example 3 is that the silicon carbide whisker is used instead of the silicon carbide whisker pre-adjuster in the preparation of the whisker compound modified dual-adjustment functional agent.

[0163] Comparative Example 3.

[0164] The difference from Example 3 is that the preparation method of the silicon carbide whisker pre-adjusting agent in the preparation of the whisker compound modified double-adjusting functional agent is different:

[0165] S01: Sodium lauryl sulfate and deionized water are mixed evenly in a weight ratio of 1:5, and then citric acid is added to account for 12% of the total amount of sodium lauryl sulfate, and stirred sufficiently to obtain a sodium lauryl sulfate solution;

[0166] S02: Add silicon carbide whiskers to a 2% hydrochloric acid solution at a weight ratio of 1:5 and stir to disperse evenly, then add sodium dodecyl sulfate solution at a weight ratio of 12% of the total amount of silicon carbide whiskers, stir to react, and after the reaction is completed, wash with water and dry to obtain a silicon carbide whisker pre-adjustment; the stirring reaction temperature is 42.5°C, the stirring time is 28min, and the stirring speed is 350r / min.

[0167] Comparative Example 4.

[0168] The difference from Example 3 is that nanocellulose is not added in the preparation method of the nano agent and the organic alcohol amine agent in the preparation of the whisker composite modified dual-adjustment functional agent.

[0169] Comparative Example 5.

[0170] The difference from Example 3 is that no lanthanum nitrate solution is added in the preparation method of the nano agent and the organic alcohol amine agent in the preparation of the whisker composite modified dual-adjustment functional agent.

[0171] Comparative Example 6.

[0172] The difference from Example 3 is that no blending modifier is added in the preparation method of the nano-agent blending the organic alcohol amine agent in the preparation of the whisker composite modified dual-adjustment functional agent.

[0173] Comparative Example 7.

[0174] The difference from Example 3 is that the parameter conditions for preparing the nano-agent and the organic alcohol amine agent in the preparation of the whisker compound modified dual-adjustment functional agent are different;

[0175] S031: Add 4.5% of the total amount of phosphate buffer solution with a pH value of 5.0 to the 12.5% ​​by mass fraction organic alcohol amine aqueous solution, and stir to mix evenly;

[0176] S032: Then add 7% of the total amount of the organic alcohol amine aqueous solution as a blending modifier, 2% of the total amount of the organic alcohol amine aqueous solution as a lanthanum nitrate solution, and then add 7.5% of the total amount of the organic alcohol amine aqueous solution as sodium humate and 1.5% of the total amount of the organic alcohol amine aqueous solution as nanocellulose to S031, and then stir at a speed of 700r / min for 35min. After stirring, the nano-agent blending organic alcohol amine agent is obtained.

[0177] Comparative Example 8.

[0178] The difference from Example 3 is that no hollow glass microspheres or fiber additives are added.

[0179] Comparative Example 9.

[0180] The difference from Example 3 is that the preparation method of the hollow glass microsphere blending fiber additive is different:

[0181] 2 parts of carboxymethyl cellulose, 3.5 parts of 5% chitosan aqueous solution and 1.0 part of wood fiber were added to 7.5 parts of hollow glass microspheres, and the mixture was sent to a ball mill for ball milling. After the ball milling was completed, the mixture was washed with water and dried to obtain hollow glass microsphere blended fiber additive.

[0182] The products of Examples 1 to 3 and Comparative Examples 1 to 9 were subjected to conventional performance tests and placed at 70°C for 2 hours to test conventional conditions and high temperature performance. The test performances include aggregate settlement (mm), number of cracks (m 2 ), 28d compressive strength (MPa) and flexural strength (MPa); the test results are as follows

[0183]

[0184] It can be seen from Comparative Examples 1-9 and Examples 1-3 that;

[0185] The aggregate settlement and the number of cracks of the product of Example 3 can achieve coordinated improvement, and the 28d compressive strength and flexural strength performance of the product are significantly improved. At the same time, the performance of the product remains stable under temperature resistance conditions.

[0186] It can be seen from Comparative Example 1, Comparative Example 8 and Example 3 that without adding one of the whisker-compounded modified double-tuning functional agent and the hollow glass microsphere-tuning fiber additive, the aggregate settlement, crack count, 28d compressive strength and flexural strength of the product are significantly deteriorated, and at the same time, the performance changes are more significant under high temperature conditions;

[0187] It can be seen from Comparative Examples 1-9 and Example 3 that under high temperature conditions, the aggregate settlement is slightly improved, but the number of cracks deteriorates significantly. This may be due to the increase in temperature, the increase in hydration rate, and the acceleration of cement curing rate, which leads to the improvement of aggregate settlement, but the number of cracks deteriorates significantly. This is due to the high temperature and heat accumulation, which easily leads to cracks.

[0188] As can be seen from Comparative Examples 2-7 and Example 3, the silicon carbide whisker pre-adjuster is replaced by silicon carbide whiskers, and the preparation method of the silicon carbide whisker pre-adjuster is different. At the same time, nanocellulose and lanthanum nitrate solution are not added in the preparation method of the nano-agent and the organic alcohol amine agent, and the reaction parameter conditions are different. The performance of the product has a trend of deterioration. At the same time, no blending modifier is added. In the preparation of the whisker composite modified double-adjustment functional agent, the performance change of the product is most obvious. The blending modifier has an important optimization effect on the performance effect of the product in the preparation of the whisker composite modified double-adjustment functional agent, and can coordinate and optimize the number of cracks and aggregate settlement of the product, and coordinate and improve the 28d compressive strength and flexural strength performance of the product.

[0189] Only the whisker compound modified double-adjustment functional agent prepared by the method of the present invention can improve the performance of the product most significantly. Other methods used instead are not as significant as the effect of the present invention.

[0190] It can be seen from Comparative Examples 8-9 and Example 3 that the performance effects of the hollow glass microspheres and fiber additives prepared by different methods on the products tend to deteriorate. Only the hollow glass microspheres and fiber additives prepared by the method of the present invention have the most significant performance effects on the products.

[0191] The present invention further explores the product performance by preparing the blending modifier;

[0192] Experimental example 1.

[0193] The only difference from Example 3 is that the surface of the carbon nanotubes is not wetted with the soaking liquid in the preparation of the blending modifier.

[0194] Experimental example 2.

[0195] The only difference from Example 3 is that the leaching liquid is replaced by a hydrochloric acid solution with a mass fraction of 8%.

[0196] Experimental Example 3.

[0197] The only difference from Example 3 is that the preparation of the modifier was not used, and the temperature was then raised to 76°C at a rate of 2°C / min and kept warm for 7.5 min.

[0198] Experimental Example 4.

[0199] The only difference from Example 3 is that the dispersion cooling process in the 5% by mass sodium alginate aqueous solution is directly replaced by air cooling.

[0200]

[0201] It can be seen from Experimental Examples 1-4 that the preparation of the blending modifier does not use the soaking liquid to wet the surface of the nano carbon nanotubes. Among the factors in the preparation of the blending modifier, the performance deterioration is the most obvious. This factor has a greater impact on the performance of the product in the preparation of the blending modifier. At the same time, the inventors of the present invention also found that the preparation of the blending modifier did not use the soaking liquid, and then the temperature was raised to 76°C at a rate of 2°C / min, and the temperature was kept for 7.5 minutes. The dispersion cooling treatment in a 5% sodium alginate aqueous solution by mass was directly replaced by air cooling, and the soaking liquid was replaced by an 8% hydrochloric acid solution by mass. The product performance effect has a tendency to deteriorate. Only the preparation of the blending modifier of the present invention has the most significant performance effect. The blending modifiers prepared by other methods are not as significant as the effects of the present invention.

[0202] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0203] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A self-compacting concrete, characterized in that: It includes the following raw materials in parts by weight: 65-75 parts of cement, 35-40 parts of fly ash, 25-30 parts of sand, 25-30 parts of crushed stone, 15-20 parts of limestone powder, 10-15 parts of whisker compound modified double-adjusting functional agent, 4-8 parts of hollow glass microspheres and fiber additives, 2-3 parts of water reducer, and 85-95 parts of water; The preparation method of the whisker composite modified double-adjusting functional agent is as follows: S01: Sodium dodecyl sulfate and deionized water are mixed uniformly in a weight ratio of 1:5, and then 10-15% of the total amount of sodium dodecyl sulfate and 2-5% of the total amount of sodium dodecyl sulfate and 6% yttrium nitrate solution are added, and stirred sufficiently to obtain sodium dodecyl sulfate solution; S02: placing the silicon carbide whisker in 3 to 5 times concentrated nitric acid for reflux pretreatment, then adding the refluxed silicon carbide whisker to a 2% hydrochloric acid solution at a weight ratio of 1:5 and stirring to disperse evenly, then adding 10 to 15% of the total amount of the refluxed silicon carbide whisker sodium dodecyl sulfate solution, stirring and reacting, and after the reaction is completed, washing with water and drying to obtain a silicon carbide whisker pre-adjustment; S03: Preparation of nano-agent and organic alcohol amine agent: S031: adding 3% to 6% of the total amount of a phosphate buffer solution with a pH value of 5.0 to a 10% to 15% mass fraction organic alcohol amine aqueous solution, and stirring to mix uniformly; S032: then add 5-9% of the total amount of the organic alcohol amine aqueous solution of the blending modifier and 1-3% of the total amount of the organic alcohol amine aqueous solution of the lanthanum nitrate solution to S031, and stir at a speed of 350-450r / min for 20-30min; S033: Finally, add 5-10% of the total amount of organic alcohol amine aqueous solution of sodium humate and 1-2% of the total amount of organic alcohol amine aqueous solution of nanocellulose to S032, and then stir at a speed of 650-750 r / min for 30-40 minutes. After stirring, the nano agent and organic alcohol amine agent are obtained; S04: Add nano-agent and organic alcohol amine agent to the silicon carbide whisker pre-adjustment according to the weight ratio of 7:2, transfer to a ball mill for ball milling, the ball milling speed is 1000-1500r / min, the ball milling is 1-2h, after the ball milling is completed, wash with water, and dry to obtain a whisker composite modified dual-adjustment functional agent; The preparation method of the blending modifier is: The carbon nanotubes are first heated to 55-60°C for 10-20 minutes, then kept warm, and the soaking liquid is sprayed on the surface of the carbon nanotubes to soak them; wherein the soaking liquid is an aqueous solution of sodium silicate with a mass fraction of 8%; Then, the temperature is raised to 75-78°C at a rate of 1-3°C / min, kept at this temperature for 5-10 minutes, and finally dispersed and cooled in a 5% sodium alginate aqueous solution at a speed of 500-700r / min for 75-85 minutes. After the treatment, the mixture is washed with water and dried to obtain a blended modifier. The preparation method of the hollow glass microsphere blended fiber additive is as follows: S11: Preparation of hydroxyapatite fibers: Mix polycaprolactone and polyethylene glycol in a weight ratio of 4:2, add the mixture into an ethanol solvent that is 5 times the total amount of polycaprolactone, and stir evenly to obtain a primary solution; Adding 15-25% of the total amount of the initial solution of nano-hydroxyapatite to the initial solution, stirring evenly, to obtain nano-hydroxyapatite body; electrospinning the nano-hydroxyapatite body under the conditions of voltage of 30-35kv and flow rate of 5-9ml / h to obtain hydroxyapatite fiber; S12: Add 1 to 3 parts of carboxymethyl cellulose, 2 to 5 parts of 5% by mass chitosan aqueous solution and 0.8 to 1.2 parts of hydroxyapatite fiber to 5 to 10 parts of hollow glass microspheres, send them into a ball mill for ball milling, wash and dry them after the ball milling is completed to obtain hollow glass microspheres and fiber additives.

2. A self-compacting concrete according to claim 1, characterized in that: The self-compacting concrete comprises the following raw materials in parts by weight: 70 parts of cement, 37.5 parts of fly ash, 27.5 parts of sand, 27.5 parts of crushed stone, 17.5 parts of limestone powder, 12.5 parts of whisker compound modified double-adjusting functional agent, 6 parts of hollow glass microsphere blending fiber additive, 2.5 parts of water reducing agent, and 90 parts of water.

3. The self-compacting concrete according to claim 1, characterized in that: The cement is one or more combinations of silicate cement, aluminate cement, sulphoaluminate cement and ferroaluminate cement; The fly ash is Class I fly ash, with a 45 μm sieve residue of ≤12% and a moisture content of ≤1.0%; the fineness modulus of the sand is 2.5-3.0, and the apparent density is 2600-2620 kg / m 3 The crushed stone is a continuously graded crushed stone with a particle size of 5 to 10 mm and an apparent density of 2650 to 2680 kg / m 3 The water reducer is a polycarboxylic acid-based high-performance water reducer with a water reduction rate of ≥30%; the particle size of the limestone powder is 2 to 2.5 mm.

4. The self-compacting concrete according to claim 1, characterized in that: The temperature of the reflux pretreatment in S02 is 65-68°C, the reflux time is 2-3h, and after the reflux is completed, the boiling water washing is repeated 2-3 times, and the treatment is completed; The stirring reaction temperature in S02 is 40-45°C, the stirring time is 25-35min, and the stirring speed is 300-400r / min.

5. The self-compacting concrete according to claim 1, characterized in that: The organic alcohol amine in the organic alcohol amine aqueous solution is one of monoethanolamine, propanolamine and butanolamine; the mass fraction of the lanthanum nitrate solution is 2-4%.

6. The self-compacting concrete according to claim 1, characterized in that: The ball milling speed of the ball milling treatment is 1000-1200 r / min, and the ball milling is 1-1.5 hours.

7. A method for preparing the self-compacting concrete according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1: Add fly ash, sand, crushed stone and limestone powder into a mixer and disperse them at a speed of 1200-1500 r / min for 5-10 minutes to prepare an aggregate agent; Step 2: Stir and mix the whisker compound modified double-adjusting functional agent, hollow glass microspheres and fiber additives evenly, then add them to the aggregate agent, then add cement to the aggregate agent, and disperse at a speed of 500-600r / min for 35-40min; Step 3: Then add water and water reducing agent to the product of step 2, and continue stirring for 10 to 15 minutes to obtain self-compacting concrete.

Citation Information

Patent Citations

  • Preparation method of modified basalt fiber-whisker reinforced silane cross-linking wear-resistant master batches

    CN108976689A

  • Cellulose nanocrystal additives and improved cementious systems

    US20160075601A1